Review of "Les Langues Hmong-Mjen (Miao-Yao): phonologie historique" - Mortensen, David (2024)
Sometimes the most useful works of scholarship are not those which present original insights into problems, but those that collect and synthesize the hard-won findings of earlier scholarship, providing a comprehensive reference which consolidates the accomplishments of the discipline. One such work is Barbara Niederer's Les longues Hmong-Mjen: phonologie historique. This book was published in 1998, but despite its great importance for Hmong-Mien studies, it has not yet (to my knowledge) been subject to a published review. This may be due in part to the relative obscurity of the Hmong-Mien language family. After all, the community of Hmong-Mien historical phonologists is not a large one. However, the central position of the Hmong-Mien (HmM) languages in the East/Southeast Asian linguistic area should make them of interest to a broad range of scholars working on other languages in that area, and Niederer's book will be of great value to such scholars.